1991
DOI: 10.1177/014107689108400412
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy after Craniotomy and the Place of Prophylactic Anticonvulsant Drugs: Discussion Paper

Abstract: A retrospective study of 1000 patients who had undergone supratentorial neurosurgery and with prolonged follow-up revealed an overall postoperative incidence of epilepsy of 17%. The incidence varied with different pathologies but anticonvulsants given prophylactically in a randomized trial did not significantly alter the incidence. Routine anticonvulsant prophylaxis cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 9 publications
2
59
0
1
Order By: Relevance
“…Pre-operative seizures attained 1/3 of study population and was comparable to frequency reported in other studies (2,12,16), while this study cohort had more early seizures than previous reports (11,12). Early seizures represent a well known risk factor for postsurgical epilepsy, as they correlate with the severity of the cerebral insult (14,20). In our study cohort incidence of late seizures (46% of study population) was quite elevated, occurring either in patients who had never experienced seizures before surgery and in subjects with pre-operative and early seizures.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Pre-operative seizures attained 1/3 of study population and was comparable to frequency reported in other studies (2,12,16), while this study cohort had more early seizures than previous reports (11,12). Early seizures represent a well known risk factor for postsurgical epilepsy, as they correlate with the severity of the cerebral insult (14,20). In our study cohort incidence of late seizures (46% of study population) was quite elevated, occurring either in patients who had never experienced seizures before surgery and in subjects with pre-operative and early seizures.…”
Section: Discussionmentioning
confidence: 71%
“…within 1 week from procedure) or late seizures (i.e. beyond 1 week) (7,20). Early seizures are the acute symptomatic ones, depending on the immediate post-traumatic effect of the neurosurgical procedure (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the reason for surgery, up to 50% patients have at least one seizure treated postoperatively (Shaw & Foy, 1991). There are no formal guidelines for routine seizure prophylaxis after neurosurgery in general.…”
Section: Seizure Management and Prophylaxismentioning
confidence: 99%
“…The overall incidence of postoperative epilepsy was 17% in a study of 1000 patients who had undergone supratentorial neurosurgery with prolonged follow up. 69) The incidence varied with different pathologies ranging from 3% for Frazier's operation to 92% for abscess as shown in Table 1.…”
Section: Risk Of Postoperative Seizuresmentioning
confidence: 99%